A qualitative study of feminist therapy in Kingston's prison for women. - Balfour, Gillian C. (University of Ottawa (Canada), 1994)
The Canadian government's Task Force Report on Federally Sentenced Women, Creating Choices (1990), presents a clear mandate for correctional reforms that provide women-centred therapeutic programming to address the issues of women's exploitation and abuse. This shift in correctional policy away from the traditional sexist and neglectful models of previous government reports is the result of a collective effort of women's groups and community services as well as the voices of the prisoners interviewed from across Canada. How have the experiences of federally sentenced women and the principles and strategies of feminist therapy emerging from the shelters for battered women and victims of sexual violence transcended the prison context? This qualitative study of five feminist counsellors in the Prison for Women discusses their analytic frameworks, principles, and strategies for working with federally sentenced women in an institutional setting. An important concern is the impact of the prison setting on the strategies of feminist therapists. As clinically trained professionals who share a feminist ideology, the therapists have created an expert discourse on the impact of childhood sexual and physical abuse upon women's behaviour. The respondents accounts of the lives of federally sentenced women reconstruct their mental health "needs" and justify their behaviour in the context of victimization.
Keywords: Women's Studies.